The Impact of Neoliberalism on Social Justice-Based Social Work Practice in Mental Health - Brown, Catrina; Baines, Donna; Doll, Kaitrin; Johnstone, Marjorie (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2025)
This article provides a critical view of the landscape of social workers’ experiences in mental health service provision in Canada. This national research project builds upon and supports the findings of a recent Nova Scotia study which found that the professional and social justice–based ethical paradigm of social work is often in conflict with the dominant biomedical model and is severely restricted by neoliberal managerial fiscal constraints on mental health service provision. Mental health social workers in Canada report a lack of professional autonomy, as well as professional disempowerment, devaluation, and a lack of decision-making opportunities in policy and approaches to practice. These results strongly suggest that, taken together, the climate of neoliberalism — with its emphasis on fiscal constraint and the rationalization of care and the corresponding biomedical, decontextualized, standardized, and individualized approach to mental healthcare — betrays social work’s social justice–based professional practice and identity, calling for the protection of the social work profession through establishing effective resistance.